Molecular simulation on the mechanical and thermal properties of carbon nanowire modified cellulose insulating paper. (1st April 2021) - Du, Dongyuan; Tang, Chao; Tang, Yujing; Yang, Lu; Hao, Jian
Abstract: The quality of transformer insulation is related to the safe and stability operation of the power grid, and the life of the transformer oil-paper insulation system mainly depends on the state of paper insulation. With the continuous improvement of the voltage level, the requirements for insulating paper are becoming higher and higher. Based on the molecular dynamics simulation technology, the effects of carbon nanowires with three different structures on the thermodynamic properties of cellulose insulating paper were analyzed from the aspects of mechanical parameters, MSD (mean square displacement), CED (cohesive energy density) and hydrogen bond. The simulation results showed that the carbon nanowires with three different structures have improved the thermodynamic properties of cellulose. Among them, the hard chiral carbon nanowires have the most significant improvement in the thermodynamic properties of cellulose. The elastic modulus, bulk modulus, and shear modulus have been increased by 30%, 25.6%, and 32.9%, respectively. It was found that the thermal stability of cellulose insulation paper modified by three different structure carbon nanowires was improved. The increase of thermal stability was mainly due to the increase of the cohesive energy density and the number of intermolecular hydrogen bonds.